What do policymakers need to know about harassment in the metaverse? - McIntosh, Verity; Allen, Catherine (Frontiers in Virtual Reality, 2024)
As immersive technologies and spatial computing paradigms move into the mainstream, public and political interest in the metaverse is growing. In some respects, the metaverse offers an exciting view of the future, one in which a global community can meaningfully connect regardless of where they are in the world. In contrast, however, early instances of 'proto-metaverse' spaces have been plagued by reports of harassment and abuse.Policymakers around the world are now considering the role that governments might play in the regulation and governance of metaverse spaces, seeking to secure protections for citizens, and criminal accountability for offenders in this fast-evolving space. This paper introduces some of the key issues for governments engaging with this topic, including the suitability of existing legislative frameworks, and consideration of a new category of harm that seeks to recognise the distinctive impact of 'conduct' abuses in metaverse environments.